Zeitschrift für Arbeitsrecht (Verlag Dr. Otto Schmidt, 2012)
Zeitschrift für Arbeitsrecht is a scientific publication for the entire field of labor and adjacent fields of law. The demands on a labor law practice are also factored into the articles. Book reviews and review essays complete the editorial program.